Analysis of the gap between actual reality and the requirements ofISO14001: 2015 A Case Study at Middle Refineries Company / Al-Dora Refinery - Mohammed Zaidan, Ibrahim; K. AL- Khateeb, Sameer (Journal of Economics and Administrative Sciences, 2020)
The Environmental Management System (EMS) according to ISO 14001: 2015 is considered one of the modern and important administrative systems in our time, as it is one of the tools of environmental management after it is an entry point for treatment or reducing environmental risks and their effects, especially the effects resulting from the oil industry, which is the main source of the trimester Environmental and waste and depletion of natural resources. The problem of the study is manifested in the weakness of the process of diagnosing and reducing the risks of environmental aspects and the resulting environmental impacts that have a clear and tangible impact on the lives of workers and the general environment. The aim of the study is to identify the extent of application of the environmental management system in (Midland Refineries Company / AlDora Refinery). This is done by determining the size of the gap in the application of the environmental specification by using the Checklist and a number of statistical analysis methods (arithmetic mean, weights, Percentages), and the diagnosis of environmental aspects. This study reached a set of results, the most important of which was a gap in the application of the above specification at a rate of (43%) resulting from a weakness in the application of most of the specifications of the company, as well as a lack of interest in the implementation of planned programs related to addressing or limiting environmental aspects and their impacts. The added value in this study is illustrated by diagnosing the strengths and weaknesses of each item of the environmental specification with setting an action plan for eliminating or reducing the gap in the researched company.